Primitive Neuroectodermal Tumor (PNET) of the Kidney with Level IV Inferior Vena Caval Thrombus: A Case Report - Murigendra B Hiremath, Vikram Prabha, Prakash Malur, Anita Borges, Rajendra B. Nerli* (Recent Research in Science and Technology, 2010)
Primitive neuroectodermal tumor (PNET) is classified as a malignant tumor of the kidney. It was first recognized by Arthur Purdy Stout in 1918, as a member of the family of â€œsmall round-cell tumorsâ€. Primitive renal localization is very rare. We report a case of Primitive neuroectodermal tumor of the kidney with level IV inferior vena caval (IVC) thrombus. Histologically, the tumor consisted of small round cells with round nuclei and scant cytoplasm.